PERAN BUMDES DALAM PEMBERDAYAAN MASYARAKAT DESA KUROLABU KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Alifin; Aidin Hudani Awasinombu; La Hatani; Eliyanti Agus Mokodompit (Jurnal Manajemen dan Kewirausahaan, 2025)
This study aims to describe the role of Village-Owned Enterprises (BUMDES) in community empowerment in Kurolabu Village, Kulisusu Utara District, North Buton Regency. The research employs a qualitative approach. Data collection methods include interviews, observation, and documentation, analyzed using interactive techniques through the stages of data collection, data reduction, data presentation, and conclusion drawing. The results indicate that BUMDES Kurolabu has been established since 2017 but has not operated optimally until 2024. BUMDES Kurolabu manages two business units: cashew nut trading and copra trading. Two factors influence the role of BUMDES in empowering the community of Kurolabu Village, Kulisusu Utara District, North Buton Regency: Supporting factors: the existence of regulations and BUMDES programs. Inhibiting factors: lack of community awareness about BUMDES business units, insufficient socialization, low community participation, limited funding, and the absence of a savings and loan unit.